A study on the impact of fuel injection parameters and boost pressure on combustion characteristics in a diesel engine using alcohol/diesel blends - VARGÜN, MUSTAFA (My University, 2023)
Engine researchers focused on alcohol fuels since the invention of diesel engines in the 1900s, and the rise in petrochemical costs in the 1970s triggered this concern. This study investigates the impacts of the injection start timing, pilot injection application, and boost air pressure increase, on combustion and exhaust emissions in a common rail diesel engine fueled with ethanol/butan-2-ol/diesel blends. The lowest combustion noise was obtained in the pilot injection application as 83.8 dB in E15B3. The results indicated that the peak point of cylinder gas pressure rose by more than 5 % in the application of pilot fuel injection and advanced injection timing, compared to conventional engine operating conditions. However, maximum CO2 and NOx were seen in the pilot injection application using FBDF as 5.7 % and 670 ppm, respectively. As alcohol rate increases in fuel blends, the average 1.3 ◦CA in the ignition delay period was increased, while the total combustion period was shortened more than 6 ◦CA. This result shows that the combustion reactions of alcohol/diesel fuels occur faster than pure diesel. However, the variation in the ignition delay and total combustion periods of the test fuels considerably reduced with pilot fuel injection application. These results indicates that pilot fuel injection may be applied very controlled according to changing engine conditions. It was calculated in statistical analysis that except for the coefficient variation of the maximum pressure increase rate, the other coefficient variation values were relatively stable and below 3 %. In addition, it was determined that the results of the finite element analysis are proportional to the pressure values obtained experimentally
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)